Assessing student preferences between on-site and on-line instruction during social distancing: Differences between undergraduate and graduate students - Smith, Wade; Robichaux-Davis, Rebecca (Advances in Social Sciences Research Journal, 2020)
This article reports the results of the phase I, multisite study, assessing preferences for traditional or on-line instruction between undergraduate and graduate students. Theses students had initially enrolled in a traditional (i.e., on-site) platform of instruction but due to the national distancing policy were instead instructed via an on-line only format. A mixed-method research design was employed using an author-developed survey instrument to assess instruction preference and two open-ended questions; the answers to which were subjected to content analysis.